RBPMS::NTRK3-rearranged sacral malignant spindle cell tumor in neurofibromatosis diagnosed by RNA sequencing: a case report and literature review - Chaopeng Chen; Bin Qi; Yuanyuan Miao; Zhujiang Zhuang; Chaowen Wang; Weiping Dai (Frontiers in Medicine, 2026)
Malignant spindle cell tumors arising in patients with neurofibromatosis are diagnostically challenging because malignant peripheral nerve sheath tumor (MPNST) and emerging NTRK-rearranged mesenchymal neoplasms may show overlapping clinical, histological, and immunophenotypic features. We report a 31-year-old man with a more than 20-year history of neurofibromatosis who presented with progressive lumbosacral pain and left lower-limb numbness. Imaging revealed a large cystic-solid sacral mass involving the S1–S2 region and extending through the sacral foramina into the pelvis. Core needle biopsy showed an intermediate-grade malignant spindle cell tumor with partial CD34 expression, strong pan-TRK positivity, increased p53 expression, and a Ki-67 labeling index up to 50% in hotspot areas. NTRK1 break-apart fluorescence in situ hybridization (FISH) was negative; however, RNA-based next-generation sequencing identified an RBPMS::NTRK3 fusion, establishing a molecularly confirmed NTRK3-rearranged spindle cell neoplasm and explaining the pan-TRK positivity as a true-positive result. The negative NTRK1 FISH reflected involvement of NTRK3 rather than NTRK1, illustrating that single-gene FISH cannot exclude an NTRK fusion. Given the large local tumor burden, neurological symptoms, high surgical morbidity, and the confirmed actionable fusion, the patient received molecularly guided entrectinib combined with palliative radiotherapy, with marked pain relief, neurological improvement, and radiological tumor shrinkage; at the most recent follow-up, approximately 7 months after starting entrectinib, he remained without evidence of disease progression. This case underscores that pan-TRK positivity should prompt confirmatory RNA-based sequencing rather than reliance on single-gene FISH; that actionable NTRK fusions may occur in the neurofibromatosis setting, where MPNST is the principal differential; and that molecularly informed multimodal therapy can benefit anatomically complex tumors, although response attribution requires caution when targeted therapy and radiotherapy are combined.